On the interaction between monetary and macroprudential policies - Alberto Martin; Caterina Mendicino; Alejandro Van der Ghote (European Central Bank (ECB), 2021)
The Global Financial Crisis fostered the design and adoption of macroprudential policies throughout the world. This raises important questions for monetary policy. What, if any, is the relationship between monetary and macroprudential policies? In particular, how does the effectiveness of macroprudential policies (or lack thereof) influence the conduct of monetary policy? This discussion paper builds on the insights of recent theoretical and empirical research to address these questions.
Keywords: E3; E44; G01; G21; 330; Financial Frictions; Capital Requirements; Systemic Risk